Manganese inhibits ATP-induced calcium entry through the transient receptor potential channel TRPC3 in astrocytes - Streifel, Karin (2012)
Chronic exposure to elevated levels of manganese (Mn(2+)) causes neuronal injury and inflammatory activation of glia. Astrocytes selectively accumulate Mn(2+), which inhibits mitochondrial respiration and increases production of reactive oxygen species. We previously reported that sub-acute exposure to low micromolar levels of Mn(2+) in primary astrocytes inhibited ATP-induced calcium (Ca(2+)) signaling, associated with decreased levels of endoplasmic reticulum Ca(2+) and increased mitochondrial Ca(2+) loads. In the present studies, we postulated that the mechanism underlying the capacity of Mn(2+) to inhibit these purinergic signals in astrocytes could be due to competition with Ca(2+) for entry through a plasma membrane channel. These data demonstrate that acutely applied Mn(2+) rapidly inhibited ATP-induced Ca(2+) waves and transients in primary striatal astrocytes. Mn(2+) also decreased influx of extracellular Ca(2+) induced by 1-oleoyl-2-acetyl-sn-glycerol (OAG), a direct activator of the transient receptor potential channel, TRPC3. The TRPC3 inhibitor, pyrazole-3, prevented ATP- and OAG-dependent transport of Mn(2+) from extracellular stores, demonstrated by a dramatic reduction in the rate of fluorescence quenching of Fura-2. These data indicate that Mn(2+) can acutely inhibit ATP-dependent Ca(2+) signaling in astrocytes by blocking Ca(2+) entry through the receptor-operated cation channel, TRPC3. Loss of normal astrocytic responses to purinergic signals due to accumulation of Mn(2+) could therefore comprise critical homeostatic functions necessary for metabolic and trophic support of neurons.